2000
DOI: 10.1287/inte.30.4.32.11642
|View full text |Cite
|
Sign up to set email alerts
|

Supply-Chain Synchronization: Lessons from Hyundai Motor Company

Abstract: One of the challenges of supply-chain management is developing ways to effectively integrate activities across organizations on the supply chain. Hyundai Motor Company developed mechanisms to coordinate production planning and scheduling activities among supply-chain members. Hyundai Motor's production-and-sales-control (P/SC) department uses regularly scheduled cross-functional meetings and scheduling policies to coordinate supply-chain activities. When implementing this process, the P/SC department overcame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 8 publications
0
39
0
2
Order By: Relevance
“…Effective coordination among all enterprises cooperating with one another in supply chain is essential to its success [25]. Lee and Whang suggested that information is a basic enabler for tight coordination [26].…”
Section: B Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective coordination among all enterprises cooperating with one another in supply chain is essential to its success [25]. Lee and Whang suggested that information is a basic enabler for tight coordination [26].…”
Section: B Coordinationmentioning
confidence: 99%
“…Clearly communicated goals across members of all hierarchy in the organization leads to efficient realization of planned objectives under given time, pressure and resources [25].…”
Section: E Communicationmentioning
confidence: 99%
“…One of the main consequences of this new configuration of the supply chain in this industry is the dramatic reduction in the number of first-tier suppliers that manufacturers work with (Veloso, 2000;Hahn et al, 2000;Nishiguchi, 1994;Hines, 1995). Veloso's study shows a reduction from 800 to 150 in six years (Veloso, 2000).…”
Section: Supplier Relationshipsmentioning
confidence: 99%
“…Karabakal et al, (2000), studied the American Volkswagen's vehicle distribution system and presented a combination of simulation and discrete optimization models to analyze the alterative designs in terms of costs and customer service level. Hahn et al, (2000), addressed the supply chain synchronization problem in Hyundai Motor…”
Section: Literature Reviewmentioning
confidence: 99%